Exploring the Impact of Leadership Characteristics on Subordinates’ Counterproductive Work Behavior: From the Organizational Cultural Psychology Perspective - Shen, Yaoping; Lei, Xinghui (Frontiers in Psychology, 2022)
Counterproductive work behavior (CWB) is extremely detrimental to an organization and its stakeholders as they impact economic efficiency and damage the atmosphere within the organization. The culture and personality of leaders can affect their behavior, psychology and ability. Leaders are in a position of authority, have resources and decision-making power, and their words and actions are noticed and imitated by employees. From a leadership perspective, an effective way to avoid CWB is to seek ways to reduce in its occurrence and escalation. First, we conducted a grounded theory study on the leadership characteristics which are the antecedent variable of CWB, and the leadership characteristics were divided into three categories: psychological, behavioral, and ability. These characteristics impact subordinates’ CWB. Second, based on the conservation of resource theory, we conducted an ecological validation of the mechanism through which leadership characteristics affect subordinates’ CWB, explored the role of work resources and personal resources in it. The results indicate that all three types of leadership characteristics have a negative effect on subordinates’ CWB, among them, the mediating effect of work resources was established, and the mediating effect of personal resources was established in some cases. Therefore, different characteristics of leaders will affect the cognitive differences of subordinates to resources, and then trigger behavioral responses of subordinates. By an advantage analysis of the three leadership characteristics on subordinates’ CWB, it is found that the three leadership characteristics are of similar importance on interpersonal CWB. However, in the effect of organizational CWB, the characteristics of leadership have obvious advantages.